Pharmacological effects of Pugionium cornutum (L.) Gaertn. extracts on gastrointestinal motility are partially mediated by quercetin - Chencan Su; Haoyu Li; Bang Chen; Cong Li; Chunxiao Zhang; Long Xu; Mei Lan; Yehua Shen (BMC, 2021)
Abstract Background The majority of global population suffer from various functional gastrointestinal disorders. Pugionium cornutum (L.) Gaertn. (PCG) is used to relieve indigestive symptoms in traditional Chinese medicine. However, little is known about the effects of bioactive components from PCG extracts on gastrointestinal motility. Methods Crude ethanol extract of PCG (EEP) was prepared from Pugionium cornutum (L.) Gaertn. Different solvents were used to prepare fine extracts from EEP, including water extract of PCG (WEP), petroleum ether extract of PCG (PEEP), dichloromethane extract of PCG (DEP) and ethyl acetate extract of PCG (EAEP). Smooth muscle cell model and colonic smooth muscle stripe model were used to test the bioactive effects and mechanisms of different PCG extracts on contraction and relaxation. Diverse chromatographic methods were used to identify bioactive substances from PCG extracts. Results EEP was found to promote the relaxation of gastric smooth muscle cell and inhibit the contraction of colonic smooth muscle strip. Among the fractions of EEP, EAEP mainly mediated the relaxation effect by stimulating intracellular calcium influx. Further evidences revealed that EAEP was antagonistic to acetylcholine. In addition, COX and NO-GC-PKC pathways may be also involved in EAEP-mediated relaxation effect. Quercetin was identified as a bioactive compound from PCG extract for the relaxation effect. Conclusion Our research supports the notion that PCG extracts promote relaxation and inhibits contraction of gastrointestinal smooth muscle at least partially through the effect from quercetin.